Penyelesaian Sengketa Pewarisan Terkait Kedudukan Anak Laki-Laki Angkat Berdasarkan Hukum Adat Batak Toba - Ginora Roma Ida Sinaga; Bambang Daru Nugroho; Fatmi Utarie Nasution (CV. Social Politic Genius (SIGn), 2022)
This study aims to examine and analyze inheritance dispute resolution related to the position of adopted son based on Batak Toba indigenous law. This research was conducted using a normative juridical approach with analytical descriptive specifications. The data obtained were then analyzed using qualitative juridical methods. The results show that the indigenous inheritance law positions the adopted son on par with the biological son. Suppose there is an inheritance dispute between the adopted son and the biological child. In that case, the inheritance dispute resolution based on the Batak Toba indigenous law can go through three stages: family deliberation, indigenous institutions, and the courts are the final stage or step that must be chosen. Most of the Batak Toba indigenous people choose dispute resolution through indigenous institutions. In this case, the chance of failure of agreement in dispute resolution through indigenous institutions is tiny because indigenous institutions involve indigenous leaders who understand and control the Batak Toba indigenous law. Therefore, it is recommended to all Batak Toba indigenous people who are in dispute to carry out a resolution through three stages based on the Batak Toba indigenous law. In addition, it is hoped that all Batak Toba indigenous community elements will supervise the implementation of dispute resolution decisions, considering that Batak Toba indigenous people prioritize and uphold the values of kinship and peace in dispute resolution.